Ilmuwan Pemikiran Pendidikan: Membangun Kebiasaan Berpikir Ilmiah, Dinamis dan Kritis terhadap Persoalan-Persoalan di Seputar Pendidikan Islam - Setyono, Darwan (Didaktika Religia, 2015)
The paper highlights Islamic education which is the one organized by Islamic boarding schools and diniyah madrasah. Ministry of Religious Affairs also organizes education from Islamic elementary schools, Islamic junior high schools, Islamic senior high schools, and Islamic tertiary education. The curriculum is the assimilation of the public school curriculum and Islamic teachings. These all provide the basis of Islamic teachings and accommodating ideas developed by intellectuals outside of Islam. Islamic education can be seen from four models. They are textual salafi, traditionalmadzhabi, modernist, and non-modernist models. Ibn Khaldun, Langgulung Hasan, Hasan al-Banna, Harun Nasution, Hashim Ash'ari are then used as references in developing Islamic education so as to produce qualified generation.